1992
DOI: 10.1068/a241155
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Cumulative Scaling Method Applied to Measuring Wealth in Indonesian Villages

Abstract: Stochastic cumulative scaling (SCS), sometimes called Mokken scaling, is a technique for converting several dichotomous variables into a single ordinal or interval measure of some latent trait. After a brief review of scaling approaches developed by Guttman and Mokken, the usefulness of SCS is illustrated by applying it to measure individual household wealth in two provinces in Indonesia: East Java and Bali. Recommendations are also offered regarding the application of SCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Zinn et al [ 15 ] applied the Mokken scaling method to asset data in Indonesia in 1992 and found that a scale could be made up from selected assets. They argued that the technique was attractive because it was easy to see the relationship between wealth scores and the list of assets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinn et al [ 15 ] applied the Mokken scaling method to asset data in Indonesia in 1992 and found that a scale could be made up from selected assets. They argued that the technique was attractive because it was easy to see the relationship between wealth scores and the list of assets.…”
Section: Discussionmentioning
confidence: 99%
“…Loevinger’s coefficients can be calculated for the fit of each individual item in the scale (H j ) and for the scale as a whole (H). The usual interpretation is that 0.3 ≤ H<0.4 implies a weak scale, 0.4 ≤ H<0.5 a medium scale and ≥0.5 a strong scale, whilst scales with H < 0.3 do not satisfy a Mokken scale [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…For many consumers and micro-entrepreneurs in SSA, conditions of resource constraints and the resulting necessity to prioritize products will apply. Moreover, in an empirical study, Zinn et al (1992) successfully applied acquisition pattern analysis to measure wealth among low-income villagers in Indonesia. Those villagers who were positioned closer to the hierarchy’s apex, that is, owning more products, were categorized as relatively wealthy.…”
Section: Theorymentioning
confidence: 99%